Village Baseline Study – Site Analysis Report Ma village-Yen Binh district, Vietnam - Hieu, Do Trong; Hoan, Le Khai; San, Le Viet; Hai, Le Van; Duong, Minh Tuan; Quyen, Luu Ngoc; Sen, Pham Thi; Ferrer, Alice J.; Tan Yen, Bui (2015)
Ma village, Vinh Kien commune, Yen Binh district, Yen Bai province has been selected to be one of Climate Smart Villages (CSVs) under the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in Southeast Asia. The village baseline survey (VBS) of Ma village, was therefore conducted as part of the baseline effort. This VBS aimed to provide baseline information at the village level about some basic indicators of natural resource utilization, organizational landscapes, and information networks for weather and agricultural information, which can be compared across sites and monitored over time. The study was conducted using the method developed and provided by CCAFS. The study’s findings show that Ma Village is rich and diverse in natural resources. There are three main resources of vital importance for the local people livelihoods, namely farmland, forest and water resources. However, improper exploitation and management have caused negative impacts on these resources. As mentioned by farmers, in the past, farmland of the village used to be very fertile, but has now become severely degraded due to overexploitation and improper management. Regarding forest resources: before 1980s, natural forests existed in large areas and consisted of valuable timber and wild animals. Today, much of the forest area has been converted to production forests or to food crop production land. Water resources, including lakes, rivers and streams have been severely polluted with pollutants from processing cassava, wood and also from animal husbandry and crop production. Degradation of water, farmland and forest resources are causing increasing challenges to agricultural production and also to other human activities. Results of farmer group discussions also demonstrate that there are 34 organizations operating in the village. Most of them are governmental. Very few are private or non-governmental organizations. The number of organizations involving in food security accounts for nearly 50%, the figure for those involving food crisis is 41.6% and in natural resources management is 25%. Those organizations working in food security and food crisis focus mainly on providing support (financial, seed and agricultural inputs) to local farmers to implement some production activities. Insufficient attention and input spent for sustainable development by these 34 organizations, especially those working in the area of natural resources management, could be one of the main reasons for the degradation and erosion of natural resources. There was no activity supporting Ma Village to develop production systems which can respond well to climate change. The study findings however show that local people are very flexible and creative, especially in exploitation of information. Among media channels, television is the most popular. Nevertheless, organizations, in particular, extension networks, Farmers’ Union, local authorities, etc., also have an important role in information dissemination. Exploitation of information from the internet and mobile phones has also been given attention, but mostly by young people only.